PENGUATAN NILAI AKHLAK: STUDI KUALITATIF PEMBELAJARAN AKIDAH AKHLAK BERBASIS CONTEXTUAL TEACHING AND LEARNING DI MADRASAH TSANAWIYAH - Amilia Mariam Ulfa; Damanhuri Damanhuri; Agus Susanti (Jurnal Bilqolam Pendidikan Islam, 2025)
This study examines the effectiveness of implementing Contextual Teaching and Learning (CTL) in strengthening the internalization of moral values in Akidah Akhlak instruction at a Madrasah Tsanawiyah. Employing a descriptive qualitative approach, data were collected through classroom observations, interviews with one teacher and three students from different grade levels, and document analysis. Data validity was ensured through triangulation to enhance the consistency and credibility of the findings. The results indicate that CTL is effective in linking moral content to students’ everyday experiences, thereby enhancing moral understanding through case studies, modelling, and value-based dialogue. However, the reinforcement of values achieved remains largely at the level of basic behavioral expression and has not yet fully developed into stable moral internalization. This limitation is influenced by the lack of structured opportunities for moral reflection, the impact of the broader social environment, and the absence of digital moral literacy integration in the learning process. This study affirms that while CTL makes a significant contribution to moral education, the expansion of pedagogical strategies and the integration of contemporary moral issues are necessary to further advance the internalization of values toward the formation of a mature and sustainable Islamic character.